Carbon pricing, carbon dividends and cooperation: Experimental evidence - Sebastian Bachler; Sarah Lynn Flecke; Jürgen Huber; Michael Kirchler; Rene Schwaiger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
Anthropogenic climate change is one of the most pressing global issues today and finding means of mitigation is of utmost importance. To this end, we investigate whether carbon taxes on their own and coupled with revenue recycling schemes (symmetric or asymmetric carbon dividends) improve cooperative behavior in a modified threshold public goods game of loss avoidance. We implement a randomized controlled trial on a large sample of the U.S. population and measure the portion of groups who successfully remain below a critical consumption threshold. We find that a carbon tax with symmetric dividends reduces harmful consumption levels, but coupling the tax with asymmetric dividends not only enhances consumption reduction but also significantly improves group cooperation in avoiding simulated climate change. Our results show that the application of a carbon tax and asymmetric carbon dividends reduces the failure rate to about one-fourth (6%), compared to the 22% observed in a baseline condition. We find that environmental attitudes, conservatism, education, and gender are significantly associated with success rates in staying below the threshold.
Keywords: C92; H23; H30; H41; Q54; 330; climate change; carbon pricing; carbon tax; carbon dividend; revenue recycling; cooperation